Effects of electroplating sludge introduction on the morphology, mineral phase and porosity evolution of fired clay bricks. (30th June 2019) - Mao, Linqiang; Wu, Yunqiu; Zhang, Wenyi; Hu, Linchao; Huang, Qingqing
Highlights: The introduction of sludge promoted pore volume and pore size of brick. Prolonging firing time decreased surface area and porosity. Heavy metals were immobilized by being incorporated into spinel structure. Abstract: The mixing of electroplating sludge in the manufacturing of fired clay products (brick or ceramics) is usually considered as the viable method to disposal of it. However, the introduction of electroplating sludge usually decreases compressive strength and promotes water absorption, which somewhat limits the application of products containing this sludge. In this study, influences of electroplating sludge introduction were examined in terms of microstructure, mineral phase and porosity, for explaining the change in the water absorption and compressive strength. The microstructure analysis showed that the morphology of bricks texture became rough and porous. The porosity of bricks increased remarkably due to the introduction of electroplating sludge. With 10 wt% of electroplating sludge being added, surface area, pore volume and pore size increased by 2, 4, 7, and 2.2 times comparing with there was no electroplating sludge added. Oppositely, prolonging firing time decreased significantly surface area, pore volume and pore size. The increase in pore volume can mainly be attributed to an increase in mesoporous. Additionally, XRD analysis showed that most of heavy metals would be incorporated into spinel structure, and most of spinel will be formed within 1 h. Both the enlarged pore and the formation of spinel are mainly responsible for the increase in water absorption and the decrease in compressive. This study given some possible explanations for the change in the water absorption and compressive strength when electroplating sludge was introduced for the manufacturing bricks or ceramics, and provided directions for finding possible solutions.